ANALYSIS OF THE DYNAMICS OF BANK DEPOSITS UNDER INTEREST RATE VOLATILITY IN THE IRAQI ECONOMY FOR THE PERIOD (2004-2024) (World Economics and Finance Bulletin, 2025)
The research aims to investigate the impact of savings and fixed interest rates on bank deposits (savings and fixed) with a comparison of which deposits are more responsive than others, by taking a series of data extending (2004-2024) in the Iraqi economy. Using the threshold model, we demonstrate regimedependent price-quantity relationships that vary across products. The study finds that interest rates rise early, decline, and stabilize, and that deposit growth becomes less volatile over time. Short-term savings deposits are simultaneously positively correlated with the savings rate, consistent with rapidly adjusting portfolios. Time deposits exhibit negative short-term movement with their announced rate, consistent with supply-driven pricing and a defense against rollovers during times of limited liquidity. These results suggest that banks should engage in savings pricing only when the policy/management rate can be maintained above the savings floor, and that the time deposit rate should be used aggressively only when the TIR is below the threshold.
Keywords: Bank deposits; interest rates; Iraqi economy; threshold model